Chapter 7 From John Yudkin to Jamie Oliver A Short but Sweet History on the War against Sugar - Meach, Rachel (Bloomsbury Academic, 2018)
Sugar and the link between its consumption and chronic disease is today's most debated dietary concern. Yet, as this chapter demonstrates, this debate is not a new one. Rather, the modern link between sugar and disease can be traced to the 1950s when a dialogue emerged in response to the post-war rise in chronic disease. Utilising published and unpublished texts of the late British nutritionist and anti-sugar campaigner John Yudkin, this chapter explores the numerous factors which shaped his ideas about sugar and the mediums used to propagate these to the public. Placing the history of advice about sugar in historical perspective, it provides an analysis of several key themes: the rise of nutrition science, the emergence of the state as a nutritional authority, the role of gender and cultural ideals in prescribing dietary advice, and the influence of commercial and professional interests in shaping public information concerning diet.